POLÍTICAS LINGUÍSTICAS DE ACOLHIMENTO PARA MIGRANTES/REFUGIADOS VENEZUELANOS EM CAMPO GRANDE/MS - Silvana Ferreira Monteiro (2022)
MONTEIRO, S.F. RECEPTION LINGUISTIC POLICIES FOR VENEZUELAN MIGRANTS/REFUGEES IN CAMPO GRANDE/MS, 2022. DissertaçãoPrograma de pós-graduação em letras estudos de linguagens. Universidade Federal de Mato Grosso do Sul, Campo Grande, MS, 2022. Refugees are people who are outside their countries of origin, forced to leave their homes in order to preserve their lives. Forced to flee, for fear of persecution, conflict, violence or subsistence circumstances. These migrants/refugees essentially seek employment opportunities and a better life. The adoption of Portuguese as the official language, despite the similarities with the languages spoken (Spanish and its variations), makes migrants' relations in the country difficult and even their entry into the labor market, and therefore the imperative need for a specific linguistic reception to this end. These individuals need individualized care. the Host Language (PLAc) goes beyond the dimensions of Foreign Language studies_ FL or the second language (L2), necessarily including the approach to professional growth, social rights and to integrate temporarily or permanently in the host country. The proposal for a Portuguese course for refugees from the Baptist church in Campo Grande-MS is based on inclusion, integration and reception. The methodology used in teaching Portuguese to migrants/refugees differs from teaching Portuguese as a foreign language, considering the whole, the society in which the student is inserted and the difficulties he faces in his daily life. In addition to the reception that must be promoted in the teaching of PLAc for refugees, it is important to insert guidelines on the issuance of documents, insertion in the work environment and in society in the teaching material. Reading and interpretation of texts such as Labor Laws, Preparation of Curriculum Vitae and other topics demanded by the target audience are essential to promote the social integration of refugees. The teacher is the central link, often the refugee's reference for dealing with adversities. The teacher mediates conflicts between the refugee and society that does not always receive them with shelter. Learning the language with the welcoming teacher gradually inserts the student into society, giving him resources to emancipate himself and find his place in this new reality. The professor often ends up going beyond his teaching duties, he is a friend, and that is welcoming. Keywords: Migrant; Refugee; Host language.